The importance of “disclosure” in relationships between physicians and pharmaceutical companies - Makowska, Marta; Jasiński, Łukasz (Annales. Etyka w Życiu Gospodarczym, 2019)
The article raises issues of transparency in relationships between doctors and drug manufacturers. It indicates how important it is as a way for physicians and the pharmaceutical industry to regain public trust. The manuscript will define the concept of disclosure. It will discuss in detail The Physician Payment Sunshine Act from the U.S., which imposes a legal obligation on pharmaceutical companies to disclose their relationships with doctors and university hospitals. The article will also show the diverse regulation of disclosure in different countries of the European Union. The situation in Poland will be also described. In the summary, there will be a discussion about the importance of disclosure for patients and the advantages and disadvantages of such regulations for physicians and drug manufacturers.